Effect of solvent, temperature and pressure on the stability of chiral and perovskite metal formate frameworks of [NH2NH3][M(HCOO)3] (M = Mn, Fe, Zn). Issue 46 (14th November 2016) - Mączka, Mirosław; Pasińska, Katarzyna; Ptak, Maciej; Paraguassu, Waldeci; da Silva, Tercio Almeida; Sieradzki, Adam; Pikul, Adam
Abstract : Chiral [NH2 NH3 ][Mn(HCOO)3 ] transforms into a polar P 21 structure at 293 K and shows magnetic order below T m = 9 K. Abstract : We report the synthesis, crystal structure, and thermal, Raman, infrared and magnetic properties of [NH2 NH3 ][M(HCOO)3 ] (HyM) compounds (M = Mn, Zn, Fe). Our results show that synthesis from methanol solution leads to perovskite polymorphs while that from 1-methyl-2-pyrrolidinone or its mixture with methanol allows obtaining chiral polymorphs. Perovskite HyFe, chiral HyFe and chiral HyMn undergo phase transitions at 347, 336 and 296 K, respectively, with symmetry changes from Pnma to Pna 21, P 63 to P 21 21 21 and P 63 to P 21 . X-ray diffraction and Raman studies show that the phase transitions are governed by dynamics of the hydrazinium ions. Low-temperature magnetic studies show that these compounds exhibit magnetic ordering below 9–12.5 K. Since the low-temperature structures of chiral HyMn and perovskite HyFe are polar, these compounds are possible multiferroic materials. We also report high-pressure Raman scattering studies of chiral and perovskite HyZn, which show much larger stiffness of the latter phase. These studies also show that the ambient pressure polar phases are stable up to at least 1.4 and 4.1 GPa for the chiral and perovskite phase, respectively. Between 1.4 and 2.0 GPa (for chiral HyZn) and 4.1 and 5.2 GPa (for perovskite HyZn) pressure-induced transitions are observed associated with changes in the zinc-formate framework. Strong broadening of Raman bands and the decrease in their number for the high-pressure phase of chiral HyZn suggest that this phase is disordered and has higher symmetry than the ambient pressure one.